ANALISIS KADAR HARA PUPUK ORGANIK BERBASIS AMPAS SAGU LOKAL MERAUKE - Diana S. Susanti; Johana A. Mendes; Yosehi Mekiuw; Mani Yusuf (Politeknik Pertanian Negeri Samarinda, 2022)
Fertilization is one of the efforts made to add nutrients in the soil and can increase plant growth and yield. Currently, organic fertilizers based on local resources have been developed considering the negative impact of excessive inorganic use. The use of fertilizers made from local resources in Merauke Regency is important to develop and study its potential. The purpose of this study was to analyze the potential combination of organic fertilizer content based on sago dregs. The study lasted for 1 month with organic fertilizer fermentation carried out at the Agrotechnology Laboratory, Faculty of Agriculture, Musamus University and the nutrient levels of organic fertilizers in the form of nitrogen, phosphorus, potassium, iron, zinc, pH, and water content were analyzed at the Biotrope Laboratory. The treatment in this study consisted of various organic materials in Merauke Regency with the main ingredients of sago dregs, namely lamtoro leaves + pig manure (P1), sago dregs + pig manure (P2), sago dregs + lamtoro leaves (P3), sago dregs + lamtoro leaves. + pig dung (P4), sago dregs + chicken manure (P5) and sago dregs + cow dung (P6). The treatment used a ratio of 2:1 (v/v) on each composition of the treatment material. The results of the analysis show that the nutrient content of organic fertilizer based on sago dregs varies depending on the composition of the material and has the potential to be used to increase crop production. The highest nitrogen, C/N and C-Organic levels were obtained in the treatment of sago dregs + pig manure, the highest phosphorus content was obtained in the treatment of sago dregs + chicken and the highest potassium was found in the composition of lamtoro leaf compost + pig manure.